SISTEM PAKAR DIAGNOSA PENYAKIT BAYI DAN BALITA BERBASIS ANDROID DENGAN MENGGUNAKAN ALGORITMA DEPTH FIRST SEARCH - Muhammad Syaifuddin; Anton Setiawan Honggowibowo (Institut Teknologi Dirgantara Adisutjipto, 2014)
It is a must for children (infants and toddlers) to get more attention due to their health because their body’s protections are not yet strong. This makes them susceptible for germs, bacteria, and viruses attacks. Those attacks cause disease. This disease symptom could appear all of sudden to the children. It makes their parents afraid, especially for those who have less sensitiveness for the symptom. For this reason, I make an application based on android smartphone expert system to provide information on type of disease, treatment, and prevention based on the symptoms given. This application uses forward chaining and backward chaining inference engine to make conclusion, and Depth First Search algorithms for searching the method. The result shows that this application could help parents in giving some information about common diseases attacked to infants and toddlers. This application facilitates them in delivering information which can be accessed anywhere as first aid for infants and toddlers who indicated disease.